Efficacy of boesenbergia rotunda treatment against thioacetamide-induced liver cirrhosis in a rat model - Abdulla, Mahmood Ameen; Salama, S.M.; Bilgen, M.; Al Rashdi, A.S. (Hindawi, 2012)
Background. Experimental research in hepatology has focused on developing traditional medicines into potential pharmacological solutions aimed at protecting liver from cirrhosis. Along the same line, this study investigated the effects of ethanol-based extract from a traditional medicine plant Boesenbergia rotunda (BR) on liver cirrhosis. Methodology/Results. The BR extract was tested for toxicity on 3 groups of rats subjected to vehicle (10% Tween 20, 5mL/kg) and 2g/kg and 5g/kg doses of the extract, respectively. Next, experiments were conducted on a rat model of cirrhosis induced by thioacetamide injection. The rats were divided into five groups and, respectively, administered orally with 10% Tween-20 (5 mL/kg) (normal control group), 10% Tween- 20 (5 mL/kg) (cirrhosis control group), 50 mg/kg of silymarin (reference control group), and 250 mg/kg and 500 mg/kg of BR extract (experimental groups) daily for 8 weeks. The rats in normal group were intraperitoneally injected with sterile distilled water (1 mL/kg) 3 times/week, and those in the remaining groups were injected intraperitoneally with thioacetamide (200 mg/kg) thrice weekly. At the end of the 8 weeks, the animals were sacrificed and samples were collected for comprehensive histopathological,coagulation profile and biochemical evaluations. Also, the antioxidant activity of the BR extract was determined and compared with that of silymarin. Data from the acute toxicity tests showed that the extract was safe to use. Histological analysis of the livers of the rats in cirrhosis control group revealed uniform coarse granules on their surfaces, hepatocytic necrosis, and lymphocytes infiltration. But, the surfaces morphologically looked much smoother and the cell damage was much lesser in those livers from the normal control, silymarin and BR-treated groups. In the high-dose BR treatment group, the livers of the rats exhibited nearly normal looking lobular architecture, minimal inflammation, and minimal hepatocyte damage, the levels of the serum biomarkers and liver enzymes read nearly normal, and these results were all comparable to those observed or quantified from the normal and silymarin-treated groups. The BR extract had the antioxidant activity about half of what was recorded for silymarin. Conclusion.The progression of the liver cirrhosis can be intervened using the ethanol-based BR extract, and the liver’s status quo of property, structure, and function can be preserved. This capability of the extract warrants further studies exploring the significance of its pharmacologic potential in successfully treating the liver cirrhosis in humans.